145k views
2 votes
Factor the expression:

-\lambda ^{3}+4\lambda ^{2}+4\lambda -16

User Komron
by
6.2k points

1 Answer

4 votes

Answer:


-(\lambda -4)(\lambda -2)(\lambda +2)

Explanation:

What we want to fator is:


-\lambda^3 + 4 \lambda^2 + 4\lambda - 16

There is no common factor, but let's factor it by grouping. The first two addends can be factor as follows:


-\lambda^3 + 4 \lambda^2 = \lambda^2(-\lambda + 4) = -\lambda^2(\lambda - 4)

the second addends can be factor as well:


4\lambda - 16 = 4(\lambda- 4).

Then our original expression can be rewritten like


-\lambda^3 + 4 \lambda^2 + 4\lambda -16=\lambda^2(\lambda - 4) + 4(\lambda - 4)

And here the
(\lambda-4) is the common factor!


-\lambda^2(\lambda - 4) + 4(\lambda - 4) = (\lambda - 4)(-\lambda^2 + 4)

Finally, we can factor the quadratic expression as a difference of squares
-\lambda^2 + 4 = 4 - \lambda^2 = (2+\lambda)(2-\lambda)

Ant we get


(\lambda - 4)(-\lambda^2 + 4)= (\lambda - 4)(\lambda + 2)(2-\lambda)

now, we can extract the negative sign from
(2-\lambda), and we get


-(\lambda -4)(\lambda -2)(\lambda +2).

User Kasakka
by
5.3k points